Assessment of the Potential for Biogas Production in Post-Conflict Rural Areas in Colombia Using Cocoa Residues - Carlos Burgos-Arcos; Diana M. Caicedo-Concha; Alberto Coz; Tamara Llano; Juan Carlos Colmenares-Quintero; Ramón Fernando Colmenares-Quintero (Energies, 2025)
This paper studies the potential of utilizing cocoa residues to address energy demands in post-conflict regions of Colombia. Through a systematic review, the findings indicate that cocoa byproducts from 170 municipalities could produce enough biogas to power a population nearing one million inhabitants. Three main residues can be obtained from processing cocoa—mucilage, cocoa bean shells, and cocoa pod husks—which are analyzed and recognized as the most significant in terms of potential biogas yield. The review highlights a considerable gap in existing research regarding the specific characteristics of cocoa residues and their biogas production rates. Additionally, this study emphasizes the need to investigate pretreatment methods for these materials, particularly cocoa pod husks, as well as the critical impact of transportation logistics. It also suggests exploring integrated valorization strategies and various energy conversion pathways. Finally, the article emphasizes the importance of establishing markets and promoting new initiatives to effectively utilize this abundant amount of waste. The insights gained from this analysis are relevant to similar regions, not only across South America but also in any cocoa-producing area worldwide.